EFEKTIVITAS MODEL PEMBELAJARAN METAPHORMING BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PADA POKOK BAHASAN PERBANDINGAN TRIGONOMETRI SUDUT BERELASI: Array - Sari, Eliza Ulva; Widodo, An Nur Ami (Jurnal Dialektika Program Studi Pendidikan Matematika, 2019)
The Student’s mathematical critical thinking ability is still low, many students are not yet completed with KKM worth 70. This study aims to to know the effectiveness of the Metaphorming learning model assisted by Mind Mapping on mathematical critical thinking ability in the subjects of comparison of related angle trigonometry. The effectiveness seen from the level of mastery of student’s mathematical critical thinking ability, the comparison of mathematical critical thinking of students experiment class with control class and the influence of student’s learning activitiy to student’s mathematical critical thinking ability. The approach is used experimental research with posttest control group design. The population in this research was the students of X grade of SMK Muhammadiyah 2 Paguyangan. In this research used sample is experimental class of X TKJ grade and control class was X TSM grade determined by Cluster Random Sampling technique. The used of data analysis were normality test, homogeneity test, equality tes average, completeness test, appellate test, regression test. The results in this the Metaphorming learning model assisted by Mind Mapping was effective on students mathematical critical thinking ability.